Immune checkpoint protein and cytokine expression by T lymphocytes in pleural effusion of cancer patients receiving anti–PD-1 therapy. (December 2019) - Ikematsu, Yuki; Tanaka, Kentaro; Yanagihara, Toyoshi; Liu, Renpeng; Inoue, Hiroyuki; Yoneshima, Yasuto; Ota, Keiichi; Iwama, Eiji; Takata, Shohei; Hata, Kentaro; Takahata, Yuriko; Wataya, Hiroshi; et al.
Highlights: We performed a study to observe patients developing PE under αPD-1 therapy. Some of patients could receive clinical benefit by continuing αPD-1 therapy. αPD-1 therapy upregulated immune checkpoint proteins on T lymphocytes in PE. Analyses of T lymphocytes in PE may predict response to αPD-1 therapy. Abstract: Objectives: Pleural effusion (PE) occasionally develops in cancer patients during treatment with antibodies to programmed cell death–1 (PD-1) or to its ligand PD-L1 (hereafter, αPD-1 therapy). Such effusion often contains infiltrated mononuclear cells, although the types of immune cell present as well as the outcome of such patients have remained unclear. Materials and methods: We performed a multi-institutional, observational study to examine the clinical outcome of patients who develop PE after the onset of αPD-1 therapy. We compared the immune cell profiles and the immune status of lymphocytes in PE as determined by flow cytometry between nine patients who developed effusion during αPD-1 therapy (αPD-1 group) and 15 patients who developed PE during treatment with other anticancer agents (control group). Results: Most mononuclear cells in PE were lymphocytes in both the αPD-1 and control groups. The frequency of both CD4 + and CD8 + T lymphocytes expressing the immune checkpoint proteins TIM-3 or TIGIT as well as that of CD8 + T lymphocytes expressing PD-L1 were increased in the αPD-1 group compared with the control group. αPD-1 therapy continued for a substantial period after the emergence of PE in six of the nine patients in the αPD-1 group, and the frequency of CD4 + T lymphocytes in PE expressing the immune checkpoint protein LAG-3 or the cytokine interkeukin-17 was lower for these patients than for those who did not receive a sustained treatment benefit. Conclusion: Our results suggest a clinical benefit of continuing αPD-1 therapy in some patients who develop PE. We found that infiltrating T lymphocytes in PE manifest a more exhausted phenotype during αPD-1 therapy than during treatment with other cancer drugs, with subpopulations of these cells characterized by specific immune checkpoint protein and cytokine expression profiles possibly contributing to the antitumor immune response.